The effect of resistance training in women on dynamic strength and muscular hypertrophy: A systematic review with meta-analysis - Hagstrom, A. D.; Marshall, P. W.; Halaki, M.; Hackett, D. A. (Sports Medicine, 2020)
Background: The effect of resistance training (RT) on adaptations in muscular strength and hypertrophy has never been examined in an exclusively female synthesis of the literature. Objective: The objectives of this study were threefold: (1) to systematically review the literature on female adaptations to RT, characterising the effect in terms of muscular strength and hypertrophy; (2) to distinguish the individual effects of intervention duration, frequency, and intensity on these adaptations via sub-analysis; (3) to draw evidence-based conclusions regarding training expectations in female populations. Methods: Three electronic databases were searched using terms related to RT combined with females or women. Random-effects meta-analyses were undertaken to estimate the effect of RT on muscular strength and hypertrophy in females. Possible predictors that may have influenced training-related effects (e.g., training intensity and volume) were explored using univariate analyses. Results: The systematic search identified 14,067 articles of which a total of 24 studies met the inclusion criteria and were eligible. Upper body strength was assessed in 15 studies, lower body strength in 19 studies, and muscular hypertrophy in 15 studies. Study duration lasted between 4 weeks and 12 months. Large-effect sizes were found for upper body strength (Hedges` g = 1.70; p < 0.001) and lower body strength (Hedges` g = 1.40; p < 0.001). Following use of the Trim and Fill method (due to presence of publication bias), a large effect still remained for upper body strength (Hedges` g = 1.07), although a medium effect was found for lower body strength (Hedges` g = 0.52). A medium effect was found for muscular hypertrophy (g = 0.52, p = 0.002). Sub-analyses revealed that the moderating variables "training frequency" and "training volume" significantly influenced lower body muscular strength (p < 0.001). "Training frequency" and "sets per exercise" moderated the RT effects on upper body strength (p < 0.01). No moderating variables were found to significantly influence muscular hypertrophy. A trend for a moderating effect on upper body strength was found for "age of participants" (p?=?0.08), whereby younger participants experienced a greater effect. A moderating effect was also observed where supervised training had a larger influence on the adaptation of lower body strength (p = 0.05) compared with unsupervised training. Methodological quality for the studies included in the review was found to be moderate. Conclusions: RT elicits large improvements in muscular strength and hypertrophy in healthy adult females. Training volume and frequency appear to be important variables that influence muscular strength.